Exploring the relationship between teacher and parent support and students’ noncognitive outcomes via Latent Profile Analysis - Yahan He; Tommy Tanu Wijaya; Akhmad Habibi; Huaqing chen; Mengfei Gao (Humanities & Social Sciences Communications)
Abstract Support from both teachers and parents is essential for shaping students’ noncognitive outcomes. Despite the acknowledged importance of both support sources, research on their combined impact remains sparse. Therefore, this study examined the patterns of combined teacher and parent support and their relationship with students’ noncognitive outcomes such as self-confidence, interest in learning, anxiety, attitude, and student activeness. We applied Latent Profile Analysis to analyze data from 274 secondary school students in China, identifying four distinct profiles of teacher–parent support: low teacher support–low parent support, medium teacher support–low parent support, high teacher support–low parent support, and high teacher support–high parent support. Analysis of variance was employed to analyze the differences in noncognitive support across these profiles, identifying significant differences in self-confidence, interest in learning, and anxiety across profiles; however, surprisingly, teacher and parent support were not significantly correlated with attitude or student activeness. This study highlights the critical role of teacher–parent support; contributes new insights for educators, parents, and schools; and underscores the necessity of personalized support tailored to individual needs.